Pediatric abdominal non-Hodgkin's lymphoma: diagnosis through surgical and non-surgical procedures - Arthur Almeida Aguiar; Luciana Cavalvanti Lima; Cláudia Corrêa de Araújo; Rodrigo Melo Gallindo (Elsevier, 2019)
Objective: To describe the success rate and the complications after procedures to diagnose abdominal non-Hodgkin's lymphoma in children and adolescents. Methods: A retrospective cross-sectional study was conducted with a population consisting of children and adolescents with abdominal non-Hodgkin's lymphoma diagnosed between September 1994 and December 2012. The sample comprised of 100 patients who underwent 113 diagnostic procedures, including urgent surgery (n = 21), elective surgery (n = 36), and non-surgical diagnosis (n = 56). Results: The most frequent procedures were laparotomy (46.9%) and ultrasound-guided core biopsy (25.6%). The rate of diagnostic success was 95.2% for urgent surgeries; 100% for elective surgeries and 82.1% for non-surgical procedures (p < 0.05). The rates of complication during the three diagnosis procedures considered were significant (p < 0.001; 95.2% of the urgent surgeries, 83.8% of the elective surgeries, and 10.7% of the non-surgical procedures). The length of time before resuming a full diet and starting chemotherapy was significantly reduced for patients who underwent non-surgical procedures when compared with the other procedures (p < 0.001). Conclusion: Non-surgical procedures for the diagnosis of pediatric abdominal non-Hodgkin's lymphoma are an effective option with low morbidity rate, allowing an earlier resumption of a full diet and chemotherapy initiation. Furthermore, non-surgical procedures should also be considered for obtaining tumor samples from patients with extensive disease. Resumo: Objetivo: Descrever a taxa de sucesso e as complicações dos procedimentos para o diagnóstico de linfoma não Hodgkin abdominal em crianças e adolescentes. Métodos: Estudo retrospectivo transversal em uma população de crianças e adolescentes com linfoma não Hodgkin abdominal diagnosticada entre setembro de 1994 e dezembro de 2012. A amostra foi composta por 100 pacientes submetidos a 113 procedimentos diagnósticos, inclusive cirurgia de urgência (n = 21), cirurgia eletiva (n = 36) e diagnóstico não cirúrgico (n = 56). Resultados: Os procedimentos mais frequentes foram laparotomia (46,9%) e biópsia guiada por ultrassonografia (25,6%). A taxa de sucesso diagnóstico foi de 95,2% para cirurgias de urgência; 100% para cirurgias eletivas e 82,1% para procedimentos não cirúrgicos (p <0,05). Houve diferença significativa entre as taxas de complicação associadas aos três grupos (p <0,001; 95,2% das cirurgias urgentes, 83,8% das cirurgias eletivas e 10,7% dos procedimentos não cirúrgicos). O tempo decorrido até o reinício da dieta plena e o início a quimioterapia foi significativamente reduzido para os pacientes submetidos a procedimentos não cirúrgicos quando comparados com os outros procedimentos (p < 0,001). Conclusão: Os procedimentos não cirúrgicos para o diagnóstico do linfoma não Hodgkin abdominal pediátrico são uma opção efetiva com baixa taxa de morbidade, permitem uma retomada mais precoce de uma dieta plena e início de quimioterapia. Em pacientes com doença extensa, os procedimentos não cirúrgicos também devem ser considerados para a obtenção de amostras tumorais. Keywords: Abdomen, Biopsy, Non-Hodgkin's lymphoma, Pediatric, Surgery, Palavras-chave: Abdome, Biópsia, Linfoma não Hodgkin, Pediátrico, Cirurgia